Worldwide Opinion on Multicenter Randomized Interventions Showing Mortality Reduction in Critically Ill Patients: A Democracy-Based Medicine Approach - Pisano, Antonio; Landoni, Giovanni; Lomivorotov, Vladimir; Comis, Marco; Gazivoda, Gordana; Conte, Massimiliano; Hajjar, Ludhmila; Finco, Gabriele; Jovic, Miomir; Mucchetti, Marta; Kunstýř, Jan; Paternoster, Gianluca; et al. (Journal of cardiothoracic and vascular anesthesia, 2016)
OBJECTIVES: Democracy-based medicine is a combination of evidence-based medicine (systematic review), expert assessment, and worldwide voting by physicians to express their opinions and self-reported practice via the Internet. The authors applied democracy-based medicine to key trials in critical care medicine. DESIGN AND SETTING: A systematic review of literature followed by web-based voting on findings of a consensus conference. PARTICIPANTS: A total of 555 clinicians from 61 countries. INTERVENTIONS: The authors performed a systematic literature review (via searching MEDLINE/PubMed, Scopus, and Embase) and selected all multicenter randomized clinical trials in critical care that reported a significant effect on survival and were endorsed by expert clinicians. Then they solicited voting and self-reported practice on such evidence via an interactive Internet questionnaire. Relationships among trial sample size, design, and respondents' agreement were investigated. The gap between agreement and use/avoidance and the influence of country origin on physicians' approach to interventions also were investigated. MEASUREMENTS AND MAIN RESULTS: According to 24 multicenter randomized controlled trials, 15 interventions affecting mortality were identified. Wide variabilities in both the level of agreement and reported practice among different interventions and countries were found. Moreover, agreement and reported practice often did not coincide. Finally, a positive correlation among agreement, trial sample size, and number of included centers was found. On the contrary, trial design did not influence clinicians' agreement. CONCLUSIONS: Physicians' clinical practice and agreement with the literature vary among different interventions and countries. The role of these interventions in affecting survival should be further investigated to reduce both the gap between evidence and clinical practice and transnational differences.
Keywords: intensive care; multicentrické studie jako téma; anesthesia; Evidence-Based Medicine; Multicenter Studies as Topic; survival; péče o pacienty v kritickém stavu; Critical Care; mortalita v nemocnicích; internacionalita; consensus conference; Randomized Controlled Trials as Topic; Humans; kritický stav; Hospital Mortality; medicína založená na důkazech; critically ill; randomizované kontrolované studie jako téma; lékaři; Physicians; mortality; Critical Illness; lidé; Internationality